Kalopanaxsaponin B Ameliorates TNBS-Induced Colitis in Mice - Jeong, Jun-Ju; Jang, Se-Eun; Joh, Eun-Ha; Han, Myung-Joo; Kim, Dong-Hyun (Biomolecules & therapeutics, 2012)
The stem-bark of Kalopanax pictus (KP, family Araliaceae), of which main constituent is kalopanaxsaponin B, has been used for asthma, rhinitis, and arthritis in Chinese traditional medicine. To clarify anticolitic effect of KP, we examined anti-inflammatory effect of KP extract and kalopanaxsaponin B in lipopolysaccharide (LPS)-stimulated peritoneal macrophage and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitic mice. Of KP extracts, KP BuOH-soluble fraction most potently inhibited LPS-induced IL-1β, IL-6 and TNF-α expression, as well as NF-κB activation. However, KP BuOH fraction increased IL-10, an anti-inflammatory cytokine. KP BuOH fraction also inhibited colon shortening and myeloperoxidase activity in TNBS-induced colitic mice. KP BuOH fraction also potently inhibited the expression of the pro-inflammatory cytokines, IL-1β, IL-6 and TNF-α as well as the activation of NF-κB. Kalopanaxsaponin B, a main constituent of KP, inhibited TNBS-induced colonic inflammation, including colon shortening, and TNBS-increased myeloperoxidase activity pro-inflammatory cytokine expression and NF-κB activation in mice. Based on these findings, KP, particularly its main constituent, kalopanaxsaponin B, may ameliorate colitis by inhibiting NF-κB pathway.